CHRONIC PURULENT OTITIS MEDIA IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic suppurative otitis media (CSOM) can occur in several variants. A more favorable form is mesotympanitis, in which there is isolated inflammation of the mucous membrane of the auditory tube, meso- and hypotympanum. In the structure of CSOM in children, mesotympanitis occupies a leading place and accounts for more than half of all cases of this disease. Another form, epitympanitis, which accounts for about 20% of CSOM cases, is characterized by a more severe course compared to mesotympanitis. With epitympanitis, the upper floor of the tympanic cavity (attic) and the mastoid process are predominantly affected, and with this form of CSOM, caries of the bone walls of the tympanic cavity, antrum, auditory ossicles necessarily occurs, cholesteatoma can form. Currently, there is no single tactic in the comprehensive rehabilitation of children with congenital cleft lip and palate (CCLP). In domestic literature and in practical healthcare, due attention is not paid to the state of the ENT organs in children with congenital cleft lip and palate and, in particular, middle ear pathology. Anatomical and functional changes accompanying congenital cleft lip and palate lead to both acute and chronic diseases of the ENT organs.